"I should have known". The perceptual barriers faced by mental health practitioners in recognising and responding to their own burnout symptoms. Issue 2 (3rd July 2019) - Ledingham, M.D.; Standen, P.; Skinner, C.; Busch, R.
ABSTRACT: Studies have shown burnout to be a significant problem in the mental health field, causing workers serious health problems and reducing quality of care provided to clients. Yet despite mental health practitioners' training in supporting others' emotional health, they may be reluctant to seek help for burnout symptoms. This paper addresses this paradox by showing how human cognitive processes could act as powerful blocks to the recognition of and response to burnout. Fifty-five mental health practitioners' beliefs and perceptions about burnout were examined using qualitative interview and survey data interpreted through a phenomenological perspective on attribution theory. The study identified four perceptual biases and identified professional identity and stress-induced cognitive deficit having influence on the recognition and response to burnout.